1976
DOI: 10.1149/1.2132934
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Oxidation of Copper in Alkaline Solutions: I . Nucleation and Growth of Cupric Hydroxide Films

Abstract: The anodic oxidation of copper in LiOH solution has been investigated by galvanostatic, potentiostatic, and voltammetric sweep techniques. The structure and composition of the films were determined by x-ray and electron diffraction, and by scanning electron microscopy. Cu(OH)2 forms in two layers: a base layer grown by a solid-state mechanism and an upper layer of individual crystals nucleated and grown from solution. The size and number of upper layer crystals are dependent on electrode potential. More anodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
1
5

Year Published

1976
1976
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 30 publications
4
61
1
5
Order By: Relevance
“…Electrochemical anodization processes were known to form a porous Cu 2 O layer at first, and then Cu(OH) 2 or CuO films on it. 27,28 Bouillon et al found that only CuO was observed at low current density (< 0.5 mA cm -2 ), and Cu(OH)2 was dominant at above 0.8 mA cm -2 . 29 In the light of these previous reports, we can interpret our results as followings: 1) at 0.1 mA cm -2 , Cu foil is covered with only the porous Cu2O particles because of a small current density for the growth of Cu(OH)2 or CuO films; 2) sheet-shape CuO mainly grows at 0.5 mA cm -2 ; 3) the growth of 1D Cu(OH)2 nanostructures, competing with the formation of CuO, become more favorable with increasing a higher current density between 1 -2 mA cm -2 .…”
Section: The Concentration Of Nucleophile Ohmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical anodization processes were known to form a porous Cu 2 O layer at first, and then Cu(OH) 2 or CuO films on it. 27,28 Bouillon et al found that only CuO was observed at low current density (< 0.5 mA cm -2 ), and Cu(OH)2 was dominant at above 0.8 mA cm -2 . 29 In the light of these previous reports, we can interpret our results as followings: 1) at 0.1 mA cm -2 , Cu foil is covered with only the porous Cu2O particles because of a small current density for the growth of Cu(OH)2 or CuO films; 2) sheet-shape CuO mainly grows at 0.5 mA cm -2 ; 3) the growth of 1D Cu(OH)2 nanostructures, competing with the formation of CuO, become more favorable with increasing a higher current density between 1 -2 mA cm -2 .…”
Section: The Concentration Of Nucleophile Ohmentioning
confidence: 99%
“…7 Various copper compound nanostructures, including nanotubes, nanowires, whiskers and nanosheets, have been grown directly by the chemical oxidation of copper foil in alkaline aqueous solutions with an oxidant additive [8][9][10][11] or by the electrochemical anodization in an alkaline solutions. 12 In particular, Xu and co-workers successfully prepared Cu(OH)2 nanowire and nanotube arrays on a copper substrate via the electrochemical route using an electrolyte solution of KOH. 13 This electrochemical method has an advantage over other methods in that the shape and atomic compositions of final copper compound films can be controlled by means of modulating the potential, reaction time, and the integrated charge passed through the cell.…”
Section: Introductionmentioning
confidence: 99%
“…L'ttape lente est la diffusion des ions (CuBr;;,), et la vitesse de la rtaction forrnCe par les Ctapes [4] et [5] est donnte par la prernikre loi de Fick, dont la forrne sirnplifite est: [6] (CuBrTi ,I, [7] v = XFD Pour sa part, I'utilisation de l'tlectrode ii disque tournant permet d'tcrire l'tquation de Levich (1 1):…”
Section: Quantite' De Bromure Cuivreux Accumulce Durantunclassified
“…La substitution de 6 dans la relation [7] donne: ou X, la charge de ou des espkces qui diffusent, est comprise entre I et 2; v, la viscositt cintrnatique, est voisine de 0,96 x lo-' cm' s-' (12); Dc,Br;;,r est le coefficient de diffusion de l'espkce CuBr,, ~u~r iou des deux espkces a la fois, selon la valeur de X; (CuBr;,,), est la concentration en cuivre a la surface de 1'Clectrode alors que o est la vitesse de rotation de l'tlectrode en radians par seconde.…”
Section: Quantite' De Bromure Cuivreux Accumulce Durantunclassified
See 1 more Smart Citation